Response of Fungal Sub-Communities in a Maize-Wheat Rotation Field Subjected to Long-Term Conservation Tillage Management - Zhang, Cunzhi; Liu, Hao; Liu, Senlin; Hussain, Sarfraz; Zhang, Liting; Yu, Xiaowei; Cao, Kaixun; Xin, Xiuli; Cao, Hui; Zhu, Anning (Frontiers in Microbiology, 2022)
Conservation tillage is an advanced agricultural technology that seeks to minimize soil disturbance by reducing, or even eliminating tillage. Straw or stubble mulching in conservation tillage systems help to increase crop yield, maintain biodiversity and increase levels of exogenous nutrients, all of which may influence the structure of fungal communities in the soil. Currently, however, the assembly processes and co-occurrence patterns of fungal sub-communities remain unknown. In this paper, we investigated the effects of no-tillage and straw mulching on the composition, assembly process, and co-occurrence patterns of soil fungal sub-communities in a long-term experimental plot (15 years). The results revealed that combine straw mulching with no-tillage significantly increased the richness of fungi but not their diversity. Differential abundance analysis and principal component analysis (PCA) indicated that tillage management had a greater effect on the fungal communities of abundant and intermediate taxa than on the rare taxa. Available phosphorus (AP) and total nitrogen (TN) were the major determinants of fungal sub-communities in NT treatment. The abundant fungal sub-communities were assembled by deterministic processes under medium strength selection, while strong conservation tillage strength shifts the abundant sub-community assembly process from deterministic to stochastic. Overall, the investigation of the ecological network indicated that no-tillage and straw mulching practices decreased the complexity of the abundant and intermediate fungal networks, while not significantly influencing rare fungal networks. These findings refine our knowledge of the response of fungal sub-communities to conservation tillage management techniques and provide new insights into understanding fungal sub-community assembly.